The legitimacy of international courts: Victims’ evaluations of the ICTY and local courts in Bosnia and Herzegovina - Hagan, John (European journal of criminology, 2017)
This paper presents the results of a 2007 survey of victims of war crimes and crimes against humanity from Bosnia and Herzegovina. We study the level of diffuse and specific support for the International Criminal Tribunal for the former Yugoslavia (ICTY) among its constituency by exploring the respondents’ views about the ICTY and the local courts in Bosnia and Herzegovina, Croatia, and Serbia. Our results show that, whereas the ICTY was the preferred decision-maker for war crimes and crimes against humanity for the majority of the respondents, ethnicity plays a strong role in the perceptions of the ICTY’s legitimacy. Compared with Croat and Serb respondents, who typically expressed little confidence in the ICTY, the Bosniak/Muslim respondents seemed to show the greatest degree of support for the ICTY. Although the majority of the respondents evaluated the ICTY as fair, the level of support for the ICTY was sharply divided across ethnic lines as well and was related to evaluations of the ICTY’s distributive fairness and procedural fairness, and to perceptions about the judges’ (lack of) political independence. The majority of the respondents evaluated only one domestic court – the Court of Bosnia and Herzegovina – as fair.